MUDANÇA DE CULTURA DE SEGURANÇA DO TRABALHO Estudo de caso em obra de construção e montagem em uma refinaria de petróleo - Duque, Ricardo Henriques Macedo (2004)
For many years, the production was priority of Petróleo Brasileiro S.A. Petrobras. After some accidents with much repercussion on press, the organization is making a great investment in health, safety and environment - HSE. Programs are being developed in these areas and the Company main objective the is to implement a HSE Management Corporate System that will let Petrobras achieves the SMS excellence in 2005. The basis of the proposed HSE System is a change of safety culture in all organization levels, disseminating the importance of risk perception, life protection and recognition of HSE as a value. In this paper, we tried to identify the organizational and safety culture components that influence the implementation of a new model in work safety at Petrobras, and more specific, at Engenharia, one of the company s Service Unit and focus of this case study. We observe that factors such as culture differences between main office and working place and the deficient information and training about HSE Program, are complicate factors to adopt new safety model at Engenharia. We also check that the working place performance depends on contractors model, and that model, many times, is not sufficient. Moreover, the company focuses are on indicators results and with urgency to gain excellence level, inciting goals are proposed to the contractors that to achieve the results, causing, for instance, subnotification of work accidents. Including, you also have the subcontractation job of companies that with frequency, don t have sufficient HSE structure to carry out the Engenharia requirement.